Comparative Physiology and Transcriptome Analysis of Young Spikes in Response to Late Spring Coldness in Wheat (Triticum aestivum L.) - Jiang, Gang; Hassan, Muhammad A.; Muhammad, Noor; Arshad, Muhammad; Chen, Xiang; Xu, Yonghan; Xu, Hui; Ni, Qianqian; Liu, Binbin; Yang, Wenkang; Li, Jincai (Frontiers in Plant Science, 2022)
Late spring coldness (LSC) is critical for wheat growth and development in the Huang-Huai valleys of China. However, little is known about the molecular mechanisms for young spikes responding to low-temperature (LT) stress during anther connective tissue formation phase (ACFP). To elucidate the molecular mechanisms associated with low temperature, we performed a comparative transcriptome analysis of wheat cultivars Yannongg19 (YN19: cold tolerant) and Xinmai26 (XM26: cold sensitive) using RNA-seq data. Over 4000 differently expressed genes (DEGs) were identified under LT conditions (T1: 4°C) and freezing conditions (T2: −4°C) compared with control conditions (CK: 16°C). The number of DEGs between two cultivars at two LT treatments (T1: 4°C and T2: −4°C) were 834, 1353, 231, and 1882 in four comparison groups (XMCK−XMT1, XMCK−XMT2, YNCK−YNT1, and YNCK−YNT2), respectively. Furthermore, to validate the accuracy of RNA-seq, 16 DEGs were analyzed using quantitative real-time RT-PCR. Several transcriptome changes were observed through KEGG pathway functional enrichment analysis in plant hormone signal transduction, circadian rhythm-plant, and starch and sugar metabolism under low temperature. In addition, 126 transcription factors (TFs), including AP2-ERF, bHLH, WRKY, MYB, HSF, and members of the bZIP family, were considered as cold-responsive. It is the first study to investigate DEGs associated with LT stress at the transcriptome level in two wheat cultivars with different cold resistance capacities. Possibly, variations in TFs regulation and starch and sucrose metabolism contribute to different cold resistance capacities in the two cultivars. Further, physiological activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) enzymes, malondialdehyde (MDA) contents, soluble sugar contents, and sucrose contents were evaluated to investigate the negative impacts of LT in both cultivars. These findings provide new insight into the molecular mechanisms of responses to low temperature and potential candidate genes that for improving wheat's capacity to withstand low temperatures.